ABO blood group and SARS‐CoV‐2 antibody response in a convalescent donor population. Issue 7 (25th January 2021) - Bloch, Evan M.; Patel, Eshan U.; Marshall, Christi; Littlefield, Kirsten; Goel, Ruchika; Grossman, Brenda J.; Winters, Jeffrey L.; Shrestha, Ruchee; Burgess, Imani; Laeyendecker, Oliver; Shoham, Shmuel; Sullivan, David; et al.
Abstract : Background and Objectives: ABO blood group may affect risk of SARS‐CoV‐2 infection and/or severity of COVID‐19. We sought to determine whether IgG, IgA and neutralizing antibody (nAb) to SARS‐CoV‐2 vary by ABO blood group. Materials and Methods: Among eligible convalescent plasma donors, ABO blood group was determined via agglutination of reagent A1 and B cells, IgA and IgG were quantified using the Euroimmun anti‐SARS‐CoV‐2 ELISA, and nAb titres were quantified using a microneutralization assay. Differences in titre distribution were examined by ABO blood group using non‐parametric Kruskal–Wallis tests. Adjusted prevalence ratios (aPR) of high nAb titre (≥1:160) were estimated by blood group using multivariable modified Poisson regression models that adjusted for age, sex, hospitalization status and time since SARS‐CoV‐2 diagnosis. Results: Of the 202 potential donors, 65 (32%) were blood group A, 39 (19%) were group B, 13 (6%) were group AB, and 85 (42%) were group O. Distribution of nAb titres significantly differed by ABO blood group, whereas there were no significant differences in anti‐spike IgA or anti‐spike IgG titres by ABO blood group. There were significantly more individuals with high nAb titre (≥1:160) among those with blood group B, compared with group O (aPR = 1·9 [95%CI = 1·1–3·3], P = 0·029). Fewer individuals had a high nAb titre among those with blood group A, compared with group B (aPR = 0·6 [95%CI = 0·4‐1·0], P = 0·053). Conclusion: Eligible CCP donors with blood group B may have relatively higher neutralizing antibody titres. Additional studies evaluating ABO blood groups and antibody titres that incorporate COVID‐19 severity are needed.